2015
DOI: 10.1127/entomologia/2015/0190
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of Bacillus thuringiensis crystalline toxins against Cydia pomonella (Linneaus) (Tortricidae: Lepidoptera)

Abstract: The purpose of this study was to evaluate potential usefulness of Bacillus thuringiensis crystalline toxin mixtures against crop pest representing the insect order Lepidoptera. Crystals of two B. thuringiensis strains, MPU B9 and MPU B63, were isolated using a gradient of sucrose density. Mixtures of crystals MPU B9/MPU B63 were prepared and their toxicity against the codling moth Cydia pomonella (Lepidoptera) was estimated. In parallel, the toxicity of separate crystal suspension of MPU B9 and MPU B63 was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Including effi cient biological control agents in pest management programs, not only provides more stable control (Lundgren et al, 2009;Aggarwal et al, 2016;Konecka et al, 2016), but compared to chemical control has benefi ts, including the pest not becoming resistant (Liang et al, ensured that all the insects tested were similar in terms of their physiological status and voracity.…”
Section: Introductionmentioning
confidence: 99%
“…Including effi cient biological control agents in pest management programs, not only provides more stable control (Lundgren et al, 2009;Aggarwal et al, 2016;Konecka et al, 2016), but compared to chemical control has benefi ts, including the pest not becoming resistant (Liang et al, ensured that all the insects tested were similar in terms of their physiological status and voracity.…”
Section: Introductionmentioning
confidence: 99%
“…There is no data about the interaction of Cry1A and Cry1D as well as Cry1B and Cry9. Konecka et al (2015) have observed synergistic activities of mixtures consisting of crystals isolated from two isolates of B. thuringiensis against C. pomonella. These mixtures displayed higher toxicity against insect than commercial biopesticide Foray based on B. thuringiensis, recommended for reduction of the number of pests in plant protection.…”
Section: Discussionmentioning
confidence: 99%
“…We determined the pesticidal activity of mixtures of B. thuringiensis MPU B9 crystals with azadirachtin and mustard oil against lepidopteran insects. We chose MPU B9 isolate because of the large number and variety of genes coding for insecticidal toxins (Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ) and the high activity of preparations based on this strain against insects (Konecka et al, , , , ; Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ). Considering the possibility of synthesising by B. thuringiensis factors harmful for vertebrates (Kim et al, ; Mac Innes & Bouwer, ; Mukry et al, ), our research was based on the analysis of the activity of preparations without spores.…”
Section: Discussionmentioning
confidence: 99%
“…The strain was used because of the high number and variety of genes coding for crystalline toxins: cry1Aa , 1B , 1C , 1D , 1I , 2Ab , 9B , 9E (Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ). Preparations based on MPU B9 isolate containing crystals (Konecka, Baranek, Kaznowski, Ziemnicka, & Ziemnicki, ; Konecka, Baranek, Ziemnicka, & Kaznowski, ; Konecka, Hrycak, & Kaznowski, ; Konecka, Ziemnicka, Baranek, & Kaznowski, ) or crystals and spores (Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ) showed high insecticidal activity against lepidopteran pests.…”
Section: Methodsmentioning
confidence: 99%